Crystal habit modification and polymorphic stability assessment of a long-acting β2-adrenergic agonist. Issue 22 (20th May 2019) - Tulcidas, Ameessa; Lourenço, Nuno M. T.; Antunes, Rafael; Santos, Bruno; Pawlowski, Sylwin; Rocha, Fernando
Abstract : Crystal habit modification of a drug substance by performing a slurry test at a temperature higher than the melting point. Abstract : Properties such as particle orientation, flowability, packing, compaction, syringeability, suspension stability and dissolution are the most influenced by changes in the crystal habit and polymorphic form of a drug substance. The crystal habit of a drug substance (long-acting β2 -adrenergic agonist (LABA)), as well as its purity and polymorphic stability, was studied after performing slurry tests with 1, 2-dimethoxyethane : heptane solution at 50 °C. In these slurry tests, the product was kept suspended and undissolved, with agitation, for polymorphic conversion evaluation. Since no significant modifications were observed in the crystal shape and dimensions at 50 °C, a new slurry test was performed at a temperature above the melting point of the starting material (80 °C). In the latter test, it was possible to obtain crystals with increased dimensions by 480% compared with the starting material. Additionally, the desired polymorphic form (form I) was obtained as well as an acceptable purity of approximately 99%. These are promising results, not only for downstream purposes, but also concerning the bioavailability of the drug substance. This work shows that working at a temperature higher than the melting point of the compound seems to modify the crystal habit of the product.